The perks of being an organic chicken – animal welfare science on the key features of organic poultry production - Göransson, Lina; Lundmark Hedman, Frida (Frontiers in Animal Science, 2024)
Modern poultry production entails a number of important animal welfare issues. However, welfare is often considered to be better in organic than in non-organic production, largely due to the focus on naturalness within the former which has been embedded within the EU regulations on organic production. The aim of this paper was to review the relevant scientific literature to assess (i) how animal welfare science relates to the key features of organic poultry production which originally stem from organic visions and ideological reasons, and (ii) whether there is scientific evidence to show that these key features, as stipulated in current EU regulations, contribute to higher welfare in organic poultry production. We identified seven key features that are intended to improve poultry welfare in organic production: appropriate breeds, no mutilations, outdoor access, natural light, perch space and raised sitting levels, provision of roughage, and lower stocking densities. In general, the animal welfare science available supports the potential for higher animal welfare in organic poultry production, based on the requirements as laid down in the current EU regulations. However, there is still room for improvement, and some aspects that may further improve animal welfare in organic poultry production include the use of alternative laying hen hybrids with the potential for better welfare, even more slow-growing broilers, appropriate management of the free-range areas in practice to ensure that they are used by the birds, additional raised sitting level space allowance for broilers, and the use of "dark brooders" for chicks.